2019
DOI: 10.1093/jn/nxz089
|View full text |Cite
|
Sign up to set email alerts
|

A Higher Mediterranean Diet Score, Including Unprocessed Red Meat, Is Associated with Reduced Risk of Central Nervous System Demyelination in a Case-Control Study of Australian Adults

Abstract: Background The evidence associating diet and risk of multiple sclerosis (MS) is inconclusive. Objectives The aim of this study was to investigate associations between a Mediterranean diet and risk of a first clinical diagnosis of central nervous system demyelination (FCD), a common precursor to MS. Methods We used data from the 2003–2006 Ausimmune Study, an A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 48 publications
(37 reference statements)
3
24
0
Order By: Relevance
“…2,30 Also, the Ausimmune case–control study, 13 from which the AusLong Study derives, has explored a range of lifestyle factors, including diet. 811,26 Our results are in keeping with the previous Ausimmune findings that a healthy diet, 8 particularly one rich in fish, 11 was inversely associated with case status. That our present study did not show a significant association between Prudent diet factor score and MS conversion risk contrasts with these results, although the focus of that analysis was an FCD, rather than MS conversion.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…2,30 Also, the Ausimmune case–control study, 13 from which the AusLong Study derives, has explored a range of lifestyle factors, including diet. 811,26 Our results are in keeping with the previous Ausimmune findings that a healthy diet, 8 particularly one rich in fish, 11 was inversely associated with case status. That our present study did not show a significant association between Prudent diet factor score and MS conversion risk contrasts with these results, although the focus of that analysis was an FCD, rather than MS conversion.…”
Section: Discussionsupporting
confidence: 92%
“…The AusLong cohort has previously examined a range of factors for their associations with clinical progression in early MS, ranging from sun and vitamin D metabolite levels 29 , BMI and dyslipidaemia 8,28 , tobacco and marijuana smoking 8 , and genetic risk factors 2,30 . Also, the Ausimmune case-control study 13 from which the AusLong Study derives, has explored a range of lifestyle factors, including diet [8][9][10][11]26 . Our results are in keeping with the previous Ausimmune findings that a healthy diet 8 , particularly one rich in fish 11 , was inversely associated with case status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few case-control studies on the dietary habits of patients suffering from MS. Epidemiological data suggest that a pro-inflammatory diet increases the risk of developing MS 23,24 , while fish oils 25 and a Mediterranean diet 26 could protect individuals from having the disease. The present study neither found any correlation between dietary habits and neurological disability, nor any significant difference between food intake by patients with MS and controls.…”
Section: Discussionmentioning
confidence: 99%
“…see literature). [1][2][3][4] Although there is little evidence associating early life diet and later MS, childhood and adolescence have been identified as periods of importance for other environmental risk factors such as obesity and low sun exposure/low vitamin D status. 5 In an Iranian study, higher consumption of various foods (fresh fish, canned tuna, poultry, cheese, yoghurt, butter, fruit and vegetables) in adolescence (13-19 years) was associated with reduced likelihood of having MS between 15 and 50 years.…”
Section: Introductionmentioning
confidence: 99%